2016
DOI: 10.2196/jmir.5270
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Discussion Forums on Pregnancy Complaints and Maternal Health Literacy in Norway: A Qualitative Study

Abstract: BackgroundThe Internet is one of the fastest growing information sources for pregnant women and seems to be used across social and economic strata. However, we still lack knowledge on how interaction in Web-based discussion forums influence maternal health literacy, in terms of how pregnant women access, appraise, and apply information to promote and maintain good health.ObjectiveThe aim of this study was to understand how Web-based discussion forums influence maternal health literacy; hence, we explored the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 23 publications
5
40
0
5
Order By: Relevance
“…We found that users critically considered information presented in this forum, engaging with and using advice and support which most resonated with personal experiences [74]. Consistent with findings from other studies, the information provided by other men in the forum (peers) appeared to be well considered, often more highly than advice from others outside the forum including health professionals or expert news sources [71,74].…”
Section: Comparison With Prior Worksupporting
confidence: 83%
See 2 more Smart Citations
“…We found that users critically considered information presented in this forum, engaging with and using advice and support which most resonated with personal experiences [74]. Consistent with findings from other studies, the information provided by other men in the forum (peers) appeared to be well considered, often more highly than advice from others outside the forum including health professionals or expert news sources [71,74].…”
Section: Comparison With Prior Worksupporting
confidence: 83%
“…Whilst it has also been reported that personal stories can be negative sources of support and not always reliable [71,75], other studies have demonstrated that most information presented in forums is actually of relatively good quality [64]. This reinforces the notion that forums are an effective platform for dissemination of health information and peer information based on personal experience is considered generally trustworthy [74].…”
Section: Comparison With Prior Workmentioning
confidence: 78%
See 1 more Smart Citation
“…In other words, women who use natural language terms in their search queries will likely stumble across forum posts at some point-or possibly even quite frequently-during their pregnancy. This is especially concerning, given that as many as 70-75% of pregnant women do not speak to their health care providers about information retrieved from the Internet [23,30,34]. Furthermore, one recent study analyzing the quality of online information in Internet discussion forums in pregnancy found that 24.3% of responses lacked credible evidence and 5.5% were potentially harmful [38].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work in the domain of digital health and pregnancy has focused on elucidating how and why women turn to digital sources during pregnancy [1,3,9,12,13,16,[19][20][21][22][23]. However, these studies have a number of limitations.…”
Section: Introductionmentioning
confidence: 99%